Effect of Storage of Yellow Pigment from Halophilic Bacillus clausii J1G-0%B on Antioxidant Activity - Galuh Dwi Arum; Mukhammad Asy'ari; Nies Suci Mulyani (Jurnal Kimia Sains dan Aplikasi, 2022)
Oxidative stress is a state of excess free radicals in the body, which results in increased oxidation processes in the body’s cells and causes damage. In previous studies, one way to neutralize this situation was found, namely with halophilic bacteria. Halophilic bacteria can live at a salt content of 2% to 30%. These bacteria can produce various kinds of pigments for self-defense from extreme environments, which function as immunomodulatory compounds and have antioxidant activity. The antioxidant activity of the yellow pigment halophilic bacteria Bacillus clausii J1G-0%B using the DPPH method showed that the effect of light and air on antioxidant activity was 17.88% inhibition in the crude extract and 14.24% inhibition at 1600 ppm. Antioxidant activity decreased by 17.13% under the influence of air, 1.89% under the influence of light, and 28.58% under the influence of air and light. FTIR analysis under the influence of air experienced a decrease in the peak of the CO carbonyl group of 1739.29 cm-1 and an increase in the alkane C-H group of 1369.52 cm-1, while under the influence of light and open conditions, the carbonyl CO group experienced an increase of 1739.50 cm-1 and 1739.46 cm-1 and the increase in alkane C-H groups 1371.41 cm-1 and 1369.53 cm- 1.